Effects of land use and land cover changes on water quality in the uMngeni river catchment, South Africa. (June 2018) - Namugize, Jean Nepomuscene; Jewitt, Graham; Graham, Mark
Abstract: Land use and land cover change are major drivers of water quality deterioration in watercourses and impoundments. However, understanding of the spatial and temporal variability of land use change characteristics and their link to water quality parameters in catchments is limited. As a contribution to address this limitation, the objective of this study is to assess the linkages between biophysico-chemical water quality parameters and land use and land cover (LULC) classes in the upper reaches of the uMngeni Catchment, a rapidly developing catchment in South Africa. These were assessed using Geographic Information Systems tools and statistical analyses for the years 1994, 2000, 2008 and 2011 based on changes over time of eight LULC classes and available water quality information. Natural vegetation, forest plantations and cultivated areas occupy 85% of the catchment. Cultivated, urban/built-up and degraded areas increased by 6%, 4.5% and 3%, respectively coinciding with a decrease in natural vegetation by 17%. Variability in the concentration of water quality parameters from 1994 to 2011 and an overall decline in water quality were observed. Escherichia coli (E. coli) levels exceeding the recommended guidelines for recreation and public health protection was noted as a major issue at seven of the nine sampling points. Overall, water supply reservoirs in the catchment retained over 20% of nutrients and over 85% of E. coli entering them. A relationship between land use types and water quality variables was found. However, the degree and magnitude of the associations varies between sub-catchments and is difficult to quantify. This highlights the complexity and the site-specific nature of relationships between land use types and water quality parameters in the catchment. Thus, this study provides useful findings on the general relationship between land use and land cover and water quality degradation, but highlights the risks of applying simple relationships or adding complex relationships in the management of the catchment. Highlights: Urban, forests and croplands had high nutrients and E. coli levels in waterbodies. The relationship between land use and water variables is complex and site-specific. The dams are significant sinks of nutrients and E. coli .